Meningkatkan Semangat Nasionalisme Melalui Pendidikan Pancasila pada Masa Pandemi COVID-19 - Yessy Tri Iswara; Arwanto Harimas Ginting (Civitas Consecratio: Journal of Community Service and Empowerment, 2022)
Pancasila education is not sufficiently implemented through general learning in schools. Another model is needed with socialization activities in which there is material presentation, quizzes and discussions in building students' understanding of nationalism with Pancasila education. This activity aims to increase the sense of nationalism among students. The method in this community service activity is by socializing with scientific discussions and using the Quizizz application. From activities found. This activity received enthusiasm from the students, especially in the discussion and use of applications. There is a new enthusiasm to find out with the desire to achieve a score in discussion activities and speed and accuracy competitions to find answers related to strengthening the spirit of nationalism. For this reason, it is necessary to carry out other activities that can foster nationalism by using advances in information technology which has now become part of the lives of students in general during the COVID-19 pandemic.